PIM kinases inhibit AMPK activation and promote tumorigenicity by phosphorylating LKB1 - Mung Kwan Long; Eccleshall William B; Santio Niina M; Rivero-Müller Adolfo; Koskinen Päivi J (BMC, 2022)
Background
The oncogenic PIM kinases and the tumor-suppressive LKB1 kinase have both been implicated in the regulation of cell growth and metabolism, albeit in opposite directions. Here we investigated whether these kinases interact with each other to influence AMPK activation and tumorigenic growth of prostate and breast cancer cells.
Methods
We first determined how PIM and LKB1 kinases affect AMPK phosphorylation levels. We then used in vitro kinase assays to demonstrate that LKB1 is phosphorylated by PIM kinases, and site-directed mutagenesis to identify the PIM target sites in LKB1. The cellular functions of PIM and LKB1 kinases were evaluated using either pan-PIM inhibitors or CRISPR/Cas9 genomic editing, with which all three PIM family members and/or LKB1 were knocked out from PC3 prostate and MCF7 breast cancer cell lines. In addition to cell proliferation assays, we examined the effects of PIM and/or LKB1 loss on tumor growth using the chick embryo chorioallantoic membrane (CAM) xenograft model.
Results
We provide both genetic and pharmacological evidence to demonstrate that inhibition of PIM expression or activity increases phosphorylation of AMPK at Thr172 in both PC3 and MCF7 cells, but not in their derivatives lacking LKB1. This is explained by our observation that all three PIM family kinases can phosphorylate LKB1 at Ser334. Wild-type LKB1, but not its phosphodeficient derivative, can restore PIM inhibitor-induced AMPK phosphorylation in LKB1 knock-out cells. In the CAM model, loss of LKB1 enhances tumorigenicity of PC3 xenografts, while cells lacking both LKB1 and PIMs exhibit slower proliferation rates and form smaller tumors.
Conclusion
PIM kinases are novel negative regulators of LKB1 that affect AMPK activity in an LKB1-dependent fashion. The impairment of cell proliferation and tumor growth in cells lacking both LKB1 and PIMs indicates that these kinases possess a shared signaling role in the context of cancer. These data also suggest that PIM inhibitors may be a rational therapeutic option for LKB1-deficient tumors.